Vectors of development in higher education of Russia and Belarus: A comparative approach - Titarenko, Larissa G. (Eastern Review, 2019)
The article is devoted to the sphere of higher education in two former Soviet countries: Russia and Belarus . It is aimed to compare the systems of higher education in these countries under the angle of global and regional challenges . The article is based on national statistics from both states and survey data . The author analyses the ways that each of the countries’ practices to increase its educational competitiveness on the global level and adapt to the market conditions . It is described that both countries use such mechanisms in the sphere of higher education as an educational service for foreign students and membership in the educational associations (European and Eurasian) . The scale of the systems of higher education and their potential are described to explain the similarities and differences between the two countries. Three types of educational integration are described . The article concludes that the system of higher education in Belarus is currently developing in a way that differs from Russia and its achievements are much smaller; at the same time, regardless of the declarations on the necessity of internationalisation, current development leads Belarus further away from the European education system, while also not make it closer to Russia . A lack of resources and political dominance over the educational goals make the Belarusian system of higher education not as attractive for students as the Russian one .